Weighting Model for Group Decision Support System: A Review - Hamdani Hamdani; Retantyo Wardoyo; Khabib Mustofa (Institute of Advanced Engineering and Science, 2018)
This paper was conducted a survey of research findings related to decision-making in groups using weighting techniques This paper conducts a survey of research findings related to decision-making in groups using weighting techniques, therefore, a new weighting model can be proposed.. In order to make a decision, this model works based on the weighting parameters, criteria or decision makers (DM) to give ranking preference in the decision results. Weighting could be done objectively or subjectively by statistical calculations. Subjective weighting based on an understanding or expertise of the decision-making process, furthermore, a numerical value was needed to make it objective. The previous weighting models need to be modified for the development of group decision support systems (GDSS). It is required to accommodate the interests of all stakeholders to link the DM relationship. We formed several groups of weighting methods that currently use for the trend of group decision-making (GDM). It showed that the classical multi-criteria decision-making (MCDM) models are still dominant in solving GDSS problems, therefore, it was necessary to apply hybrid MCDM with an approach method of stakeholders models and social networks (SN) to improve decision model that has been applied in the previous research.